A Markov regime-switching model for the semiconductor industry cycles - Liu, Wen-Hsien; Chyi, Yih-Luan (Economic modelling, 2006)
Because of the huge fluctuation in the semiconductor business, it has been a challenging work for the industry researchers to predict the turning points of the semiconductor industry cycles. To catch the cyclical behavior of the semiconductor business, we propose a Markov Regime-Switching model with two regimes representing expansion and contraction. The simple nonlinear, two states, regime-switching model shows a successful in-sample prediction on the contraction of semiconductor industry sales during the period of 1990:01–2003:08.